Rule of UA on Cardiac Myocytes Uric Acid Differently Influence the Oxidative Damage Induced by Acute Exposure of High Level of Glucose in Chicken Cardiac Myocytes - Sun, Xiaolong; Jiao, Hongchao; Zhao, Jingpeng; Wang, Xiaojuan; Lin, Hai (Frontiers in Veterinary Science, 2020)
ABSTRACT Background: Uric acid (UA) is a potent scavenger of oxidants in mammalian and avian species. In humans, hyperglycemia with simultaneous hyperuricemia may exert additional damage to the cardiovascular system. Chickens naturally have hyperglycemia (10.1 - 11.0 mmol/L) and hyperuricemia (100 - 900 µmol/L), which makes them an interesting model. Methods: The aim of this study was to investigate the effects of UA on the oxidative damage induced by acute exposure of high level of glucose in chicken cardiac myocytes. Results: Cell viability and the concentrations of thiobarbituric acid reactive substance (TBARS) were decreased by glucose treatment in a dose- and time-dependent manner. After acute exposure to high level of glucose (300 mM), a moderate level of UA (300 M) increased cell viability and reduced TBARS and glutathione (GSH) content. Compared to the control or to independent high glucose (300 mM) or UA (1200 M) treatment, the concurrent treatment of high glucose and high UA significantly increased the TBARS, protein carbonyl contents, and ROS concentration, whereas it decreased the cell viability, superoxide dismutase (SOD) activity, and GSH content. In the presence of high glucose and UA, the nucleic protein expression of nuclear factor erythroid 2-related factor 2 (Nrf2) was decreased and the mRNA levels of the genes cat, sod1, sod2, gss, and gclc were downregulated. Conclusion: In conclusion, acute exposure of high level of glucose induced oxidative damage in the cardiac myocytes of chicken. The present result suggests that an adequate level of uric acid is helpful in alleviating the acute oxidative damage that is induced by high glucose, whereas the inhibition of the Nrf2 pathway by a high level of uric acid may render the cardiac myocytes more vulnerable to suffering from oxidative damage.